Structural Characterization of Natural Yeast Phosphatidylcholine and Bacterial Phosphatidylglycerol Lipid Multilayers by Neutron Diffraction - Luchini, Alessandra; Corucci, Giacomo; Chaithanya Batchu, Krishna; Laux, Valerie; Haertlein, Michael; Cristiglio, Viviana; Fragneto, Giovanna (Frontiers in Chemistry, 2021)
Eukaryotic and prokaryotic cell membranes are difficult to characterize directly with biophysical methods. Membrane model systems, that include fewer molecular species, are therefore often used to reproduce their fundamental chemical and physical properties. In this context, natural lipid mixtures directly extracted from cells are a valuable resource to produce advanced models of biological membranes for biophysical investigations and for the development of drug testing platforms. In this study we focused on single phospholipid classes, i.e. Pichia pastoris phosphatidylcholine (PC) and Escherichia coli phosphatidylglycerol (PG) lipids. These lipids were characterized by a different distribution of their respective acyl chain lengths and number of unsaturations. We produced both hydrogenous and deuterated lipid mixtures. Neutron diffraction experiments at different relative humidities were performed to characterize multilayers from these lipids and investigate the impact of the acyl chain composition on the structural organization. The novelty of this work resides in the use of natural extracts with a single class head-group and a mixture of chain compositions coming from yeast or bacterial cells. The characterization of the PC and PG multilayers showed that, as a consequence of the heterogeneity of their acyl chain composition, different lamellar phases are formed.